Relationship between Motivation of the Midwife and the Mother's Compliance with Complete Basic Immunization in the Hana Kasih Clinic - Hasanah, Dwi Ris; Tampubolon, Emelia (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2022)
Health problems, especially in children, are the occurrence of several infectious diseases such as Measles, Diphtheria, Pertussis, Tetanus Neonatorum, Tuberculosis, Hepatitis B and Polio which can cause death or disability in children. There are still many mothers who do not take their children to health facilities to get complete basic immunizations. The role of midwives in providing motivation to families, especially mothers about immunization status, is thought to be able to increase maternal compliance to increase the coverage and completeness of basic infant immunization. The research method uses analytic with a cross sectional approach. The population in this study were 112 people and a sample of 53 people. The results showed that the motivation of the midwives according to mostly good was 54.7%, which stated that it was less than 45.3%. Mother's adherence to complete basic immunization for infants in the obedient category was 73.6%, those who did not comply were 26.4%. The motivation of the midwife is related to maternal compliance with complete basic immunization for infants at the Hana Kasih Clinic in 2021, p-value of 0.000 <0.05. It is hoped that midwives will motivate mothers, especially mothers who have babies, to immunize their babies with the 5 (five) basic immunizations required by the government.